2019
DOI: 10.1088/1361-6455/ab1df5
|View full text |Cite
|
Sign up to set email alerts
|

Target dependence of post-collision effects in ionization by proton impact

Abstract: We have measured and calculated double differential cross sections for ionization of Ne and Ar by 75 keV proton impact for a broad range of fixed projectile energy losses as a function of scattering angle. Along with data obtained previously for lighter targets this made possible a systematic analysis of post-collision effects between the scattered projectile and the continuum electron in the exit channel as a function of the target ionization potential. The data are consistent with an increasing strength of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…If this is indeed the case one would have to conclude that near the cusp energy PCI proceeds mostly through the V pe -V te -V pe sequence and that the V pe -V pt -V pe sequence is overestimated in the CDW-EIS-PT and 3DW-EIS models. Indications for such an overestimation were also found in the FDCS for ionization of H 2 [24] and in the DDCS for ionization of Ne and Ar [33].…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…If this is indeed the case one would have to conclude that near the cusp energy PCI proceeds mostly through the V pe -V te -V pe sequence and that the V pe -V pt -V pe sequence is overestimated in the CDW-EIS-PT and 3DW-EIS models. Indications for such an overestimation were also found in the FDCS for ionization of H 2 [24] and in the DDCS for ionization of Ne and Ar [33].…”
Section: Resultsmentioning
confidence: 70%
“…Instead, measured DDCS as a function of projectile energy loss and scattering angle seemed to suggest that PCI actually becomes stronger with decreasing I [16,27]. On the other hand, as mentioned in the introduction, a follow-up study on DDCS for heavier targets [33] suggested that effects due to PCI could be masked by those due to another higher-order mechanism, involving the PT interaction, but only a single projectile-electron interaction (for simplicity, we refer to this process as the second-order PT process). Therefore, the dependence of PCI effects on I could not be conclusively determined from DDCS measurements.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Significant differences between theory and experiment were found. [3,25,26] This shows that in the region of electron-projectile velocity-matching, the differential cross section is very sensitive to the details of the underlying few-body dynamics. The research of this kind of situation has aroused the great interest of more and more experimental and theoretical workers.…”
Section: Introductionmentioning
confidence: 98%